PENGARUH VARIASI DOSIS PUPUK ORGANIK CAIR LIMBAH CANGKANG TELUR AYAM (Gallus gallus domesticus), TERHADAP PERTUMBUHAN TANAMAN BAYAM MERAH (Amaranthus tricolor) - Fitrotin Rahayu; HRA Mulyani; Agil Lepiyanto (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2020)
The objectives of this study were 1) to determine the effect of variations in the dosage of liquid organic fertilizer from chicken egg shell waste on the growth of red spinach plants, 2) to determine the effect of the best dose variations that had an effect on the growth of red spinach plants, 3) to determine whether or not brochure was feasible. to serve as a learning resource for students. This type of research is experimental, this study uses a complete randomized block design (RAKL) with 6 treatments and 5 groups and 2 replications. Treatment A 20 ml / L, treatment B 40 ml / L, treatment C 60 ml / L, treatment D 80 ml / L, treatment E 100 ml / L and control 40 ml / L. To determine the effect of liquid organic fertilizer from chicken egg shell waste, data analysis was carried out using parametric tests (normal data). , non-parametric test (abnormal data) and further tests to find out the most optimum treatment for red spinach growth.. The parameters observed in this study were plant height (cm), number of leaves (strands) and red spinach plant wet weight (grams). Based on the results of the study it can be concluded that there is a significant effect of giving liquid organic fertilizer from chicken eggshell waste to height growth, number of leaves and plant wet weight.